Interprofessional Collaboration On Non-Communicable Disease Programs (NDP) In Primary Health Services - Rahmanida, Nindya; Bachtiar, Adang (Green Publisher Indonesia, 2022)
This study aims to discuss interprofessional collaboration in the Non-Communicable Disease program and the factors that influence interprofessional collaboration in the program. The research method used in this study is a qualitative descriptive method. The type of data used in this research is qualitative data, which is divided into primary data and secondary data. The results showed that interprofessional collaboration is a strategy to achieve the desired quality of results effectively and efficiently in health services. Communication in collaboration is an important element to improve service quality and patient safety. A non-communicable disease (NCD) is a disease or medical condition that cannot be passed from one individual to another. Most NCDs occur in low- and middle-income countries. Based on WHO data, NDP was the cause of 68% of deaths in the world in 2012. Interprofessional collaboration at Posbindu NDP Puskesmas is carried out by the PNDP Program Holder. Other Puskesmas officers are only involved in determining the schedule for implementing activities so that they do not conflict with the schedule of other Puskesmas activities. Planning is done in writing with a planning format from the Treasurer of the Health Center. However, this plan is only related to the development and service activities of the NDP Posbindu. The factors that influence interprofessional cooperation in the NDP program are cooperation, communication, ethics, and the role of the profession.